Metagenomic Analysis of Bacteria Phylum Firmicutes and Bacteroidetes in Women with Type 2 Diabetes - Zulhaerati Zulhaerati; Sri Budiarti; Rika Indri Astuti (Bogor Agricultural University, Indonesia, 2019)
Diabetes mellitus (DM) is a serious health problem in Indonesia. Type 2 diabetes is a metabolic disease which primarily caused by obesity-linked insulin resistance. There is a link between insulin resistance and bacterial populations in the gut. Therefore, the aims of this study was to analyze composition of bacteria belong to the phylum Firmicutes and Bacteroidetes in women with type 2 diabetes and non-diabetic persons as control. The study included five female adults type 2 diabetes patients and five healthy controls. The bacteria composition was analyzed for abundance by denaturing gradient gel electrophoresis (DGGE). Metagenomic analysis based on 16S rRNA gene was represented by 12 DGGE bands. The twelve respective bands showed the similarity ranging from 77 up to 98%. Diversity of microbial composition in women type 2 diabetes was represented by five DGGE bands are Bacteroides fragilis, Bacteroides vulgatus, uncultured Bacteroides sp. clone Lb4eF4, uncultured bacterium clone 16sms90-5g05, and uncultured bacterium clone Malaga 1F14. Four DGGE bands in women healthy controls are closely related to uncultured bacterium isolate DGGE gel band Eub42, uncultured bacterium isolate DGGE gel band K115, uncultured bacterium clone HFV04255, and Enterococcus sp. the finding shows bacterial species belong to the phylum Bacteroidetes was mostly found in women diabetic group, while those belong to the phylum Firmicutes was mostly found in healthy controls.